1978
DOI: 10.1111/j.1365-2230.1978.tb01497.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of barrier function and lipids in psoriasis and essential fatty acid-deficient rats

Abstract: Summary Elevated rates of transepidermal water loss (TEWL) in plaques of human psoriasis and in the skin of essential fatty acid (EFA)‐deficient rats were compared. Cutaneous application of sunflower seed oil to EFA‐deficient rats lowered the rate of TEWL to normal, healed the characteristic scaly skin of this condition and increased the incorporation of linoleic acid of the sunflower seed oil into epidermal phospholipid. Application of sunflower seed oil to psoriatic skin did not lower the TEWL, nor produce c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Whether or not BMI is related to other dermatologic disorders, like atopic dermatitis, hidradenitis suppurativa and dermatitis herpetiformis, is controversial (8,9,13,14). The effects of nutrition on the epidermal barrier were previously examined in mice (15)(16)(17)(18). In these studies, inappropriate nutrition led to a change in the epidermal barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Whether or not BMI is related to other dermatologic disorders, like atopic dermatitis, hidradenitis suppurativa and dermatitis herpetiformis, is controversial (8,9,13,14). The effects of nutrition on the epidermal barrier were previously examined in mice (15)(16)(17)(18). In these studies, inappropriate nutrition led to a change in the epidermal barrier.…”
Section: Discussionmentioning
confidence: 99%
“…However, oral treatment and topical treatment in randomized and double‐blind studies could not support the effect on moderate psoriasis 21,22 . Topical treatment with sunflower seed oil (rich in linoleic acid) increased the level of linoleic acid of the epidermal phospholipids, but did not improve the disease or change transepidermal water loss (TEWL) 23 …”
mentioning
confidence: 99%
“…It is generally regarded that molecules >400 Da are unsuitable for transdermal delivery 54 . However, in psoriasis patients it has been demonstrated that measures of transdermal molecular trafficking are increased 55 , 56 , thus the >400 Da cutoff may not strictly apply in this context. Furthermore, a variety of skin penetration techniques exist to overcome this obstacle including chemical techniques (e.g., permeation enhancers such as alcohols, amines, surfactants, esters, lipid-systems, or pro-drug formulations) and physical techniques (e.g., iontophoresis, electroporation, and microporation).…”
Section: Discussionmentioning
confidence: 99%